The Impact of Causal Ambiguity on Competitive Advantage and Rent Appropriation - Ambrosini, Veronique; Bowman, Cliff (Blackwell Publishing Ltd, 2010)
We seek to develop the conceptual and practical understanding of causal ambiguity. Specifically we extend current thinking by setting out three types of causal ambiguity, based on whether firm resources are perceived to display linkage and/or characteristic ambiguity, and by examining for each type the impact of causal ambiguity on the sustainability of competitive advantage and on rent appropriation. We highlight the difficulties decision-makers face when they perceive ambiguity and finally we explore some implications of ambiguity with respect to resource-creation processes.